Determinants of Quality of Life and Return to Work Following Acute Respiratory Distress Syndrome: A Systematic Review - Dodoo-Schittko, Frank (Dtsch Arztebl Int, 2017)
BACKGROUND: Acute respiratory distress syndrome (ARDS) in adults is a consequence of lung damage caused by either pulmonary or extrapulmonary disease. Survivors often suffer from an impaired health-related quality of life (HRQoL), mental and physical impairments, and persistent inability to work. METHODS: In this systematic review of the literature, we consider the determinants of HRQoL and return to work (RtW). 24 observational studies showing a statistical association between one or more determinants and HRQoL or RtW were included. Because of the heterogeneity of these studies, no statistical aggregation of the individual effect estimates was carried out; instead, the results are summarized descriptively. RESULTS: Psychopathological manifestations, in particular, are associated with impaired quality of life. In contrast, many care- and disease-related determinants had only small, non-significant effects on HRQoL and RtW. The one-second capacity was found in all studies to be positively associated with the HRQoL. ARDS induced by sepsis seems to be a risk factor for a lower HRQoL in comparison to ARDS of other causes. A synthesis of the evidence is impeded both by the high level of heterogeneity of studies and by the high risk of selection bias in all studies. CONCLUSION: The identification of determinants of impaired quality of life after ARDS is essential for the assessment of clinically relevant interventions. In multiple studies, major significant effects were only observed when determinants the content of which was closely related to the scales of the HRQoL instruments were measured at the same time as the HRQoL.